Development of Magnet‐Driven and Image‐Guided Degradable Microrobots for the Precise Delivery of Engineered Stem Cells for Cancer Therapy. Issue 41 (20th September 2020) - Wei, Tanyong; Liu, Jiang; Li, Dongfang; Chen, Shuxun; Zhang, Yachao; Li, Junyang; Fan, Lei; Guan, Zhangyan; Lo, Chung‐Mau; Wang, Lidai; Man, Kwan; Sun, Dong
Abstract: Precise delivery of therapeutic cells to the desired site in vivo is an emerging and promising cellular therapy in precision medicine. This paper presents the development of a magnet‐driven and image‐guided degradable microrobot that can precisely deliver engineered stem cells for orthotopic liver tumor treatment. The microrobot employs a burr‐like porous sphere structure and is made with a synthesized composite to fulfill degradability, mechanical strength, and magnetic actuation capability simultaneously. The cells can be spontaneously released from the microrobots on the basis of the optimized microrobot structure. The microrobot is actuated by a gradient magnetic field and guided by a unique photoacoustic imaging technology. In preclinical experiments on nude mice, microrobots carrying cells are injected via the portal vein and the released cells from the microrobots can inhibit the tumor growth greatly. This paper reveals for the first time of using degradable microrobots for precise delivery of therapeutic cells in vascular tissue and demonstrates its therapeutic effect in preclinical test. Abstract : A magnet‐driven and image‐guided degradable microrobot is developed to achieve precise delivery of engineered stem cells in vivo. The microrobot meets the requirements of degradability, mechanical strength, and magnetic drive. Guided by photoacoustic imaging, microrobots successfully deliver cells to a targeted site for tumor treatment in mice. This study verifies the feasibility of magnetic microrobots in wireless and minimally invasive surgery.